Data for 'Robust Enhancement of Tropical Convective Activity by the 2019 Antarctic Sudden Stratospheric Warming' - Noguchi, Shunsuke (Zenodo, 2020)
These data were used for making plots in the manuscript entitled 'Robust Enhancement of Tropical Convective Activity by the 2019 Antarctic Sudden Stratospheric Warming'. DOI:10.1029/2020GL088743. Data format is NetCDF.